Impact of visceral obesity on operative outcomes of laparoscopic nephrectomy: comparison between visceral fat area and body mass index - Tateki Yoshino; Shota Oshima; Tomoyuki Sugitani; Yusuke Kobayashi; Kazuo Kawakami; Koji Kodama; Hideyuki Onuma; Hiroaki Yasumoto; Hiroaki Shiina; Yasuhisa Hasegawa (African Journal of Urology, 2021)
Abstract Background Obesity has been considered as a risk factor influencing operative difficulty. It was reported that body mass index (BMI; kg/m2) did not always properly reflect the degree of a patient’s visceral fat. The purpose of this study is to retrospectively investigate the association of operative outcomes and obesity indices including visceral fat area (VFA; cm2) and BMI in retroperitoneoscopic nephrectomy (RN). Methods We retrospectively reviewed consecutive 96 RN procedures performed from September 2016 to June 2020. We divided patients into BMI obese group (BMI ≥ 25, n = 25) and BMI normal group (BMI < 25, n = 71), VFA obese group (VFA ≥ 100, n = 54) and VFA normal group (VFA < 100, n = 42). Patient characteristics, operative and postoperative outcomes were compared between the two groups for each index of obesity. Results In two groups divided by BMI, the only specimen weight was significantly greater in the obese group (320 vs. 460 g, p < 0.001), whereas VFA obese group had longer insufflation time (165 vs. 182 min, p = 0.028), greater estimated blood loss (34 vs. 88 ml, p = 0.003) and greater specimen weight (255 vs. 437 g, p < 0.001) than VFA normal group. In a logistic regression analysis, high VFA value was a significant predictor for greater specimen weight and high VFA value and large size of renal tumor were significant predictors for greater blood loss. By contrast, BMI was not a significant predictor. Furthermore, in the case of non-obese patients (BMI < 25), VFA obese group had significantly longer insufflation time, greater estimated blood loss and greater specimen weight than normal group. Conclusions The present data suggest that VFA is a more useful parameter than BMI for predicting the operative difficulty associated with obesity, and VFA has a higher use value in non-obese patients (BMI < 25) than in obese patients (BMI ≥ 25).